(untitled) (Research, Society and Development, 2020)
This study was carried out to investigate the effects of addition Baccharis dracunculifolia leaves in nature on animal performance, feed intake, ingestive behavior, and blood parameters of Nellore steers finished in feedlot on high-grain diets. A total of 40 Nellore steers, with an average body weight of 412.9 ± 22.0 kg were distributed in individual pens, equipped with automatic drinkers and masonry feeders. The steers were randomly assigned to one of four studied diets, therefore the CONT – basal diet; BAC05 – basal diet and inclusion of B. dracunculifolia leaves in natura (5 g/animal/day); BAC10 – basal diet and inclusion of B. dracunculifolia leaves in natura (10 g/animal/day); and BAC15 – basal diet and inclusion of B. dracunculifolia leaves in natura (15 g/animal/day). The use of plants in nature did not affect final body weight, average daily gain, dry matter intake, or feed efficiency. Neither on ingestive behavior activities and plasma concentrations of urea, creatine, aspartate aminotransferase, gamma-glutamyl transferase, and creatine kinase no effects were detected between diets. The inclusion of plants in nature in steer’s diet did not negatively impact performance and health. However, further field studies with beef cattle are needed for greater clarification of its effects and dosages.